Evaluation in Taiwan: An Overview - Shu-tung Huang (The Evaluation Center at Western Michigan University, 2006)
There are two tremendous influences on evaluation-related topics in Chinese society: external examination and Confucianism. Using oral and written tests to select individuals for positions in the civil service and the military generally used competitive group examinations and could be tracked back to the Western Zhou Dynasty (1027-711 BC) (Kellaghan & Madaus, 2003). Such public examination systems have deeply affected what standards to use in assessing the individual's performance, and how to do it, in Chinese society. Also, Confucianism (circa 551-479 BC), the most important ancient religious underpinning for the social values, institutions, and transcendent ideals of traditional Chinese society, has influenced the educated Chinese approach to self-reference and correction of the flaws of his/her conduct. In one of Confucius' famous analects; Zeng Zi, one of Confucius' students, said: "I examine myself three times a day about whether I help my peers with all my efforts, whether I am honest and faithful to my friends, and whether I practice what is imparted." The way of self-reflection has been rooted in how to improve one's morality, behavior, and problem-solving skills.